Peran Sunan Gresik Dalam Pengembangan Pendidikan Islam di Jawa - Sibli, M. Imam; Misbah, Nizzalul; Kusno, Moh. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Qomaruddin, Gresik, Indonesia, 2025)
Sunan Gresik, or Shaikh Maulana Malik Ibrahim, is one of the central figures in the history of the spread of Islam in Java, especially in the context of Islamic education. This research aims to explore Sunan Gresik's contribution to the development of Islamic education, as well as its impact on the character and intellectual formation of Javanese society. Using a qualitative approach with library study methods, this research analyzes various sources, including historical texts, academic literature, and related documents, to formulate Sunan Gresik's role as an educator and innovator in the world of Islamic education. The research results show that Sunan Gresik not only focuses on spreading Islamic teachings, but also realizes the importance of education as a means of advancing society. He founded the Islamic boarding school as an educational institution which became a center for teaching religious knowledge and instilling moral values. The teaching method used by Sunan Gresik emphasizes the integration of Islamic teachings with local wisdom, making it easier for people to understand and practice religious teachings. The impact of this educational reform was seen in the growth of an educated and ethical Muslim community, which later became the foundation for the development of Islam in Java.